The Effect of Continuous Education on the Professional Practice of French Community Pharmacists - Calop, N.; Allenet, B.; Calop, J.; Figari, G. (Pharmacy Education, 2002)
In order to maintain a high quality pharmaceutical system, pharmacists should be engaged in continuous education. The purpose of this study is to evaluate the impact of a continuous training scheme on pharmacists’ practices concerning the validation of prescriptions. We used an educational methodology, through exploratory talks and literature on this issue, to build an adapted questionnaire. Results show: (1) a potential improvement in the relationship between pharmacists and physicians; (2) the pharmacists’ awareness of their essential role for the prevention of iatrogenic risk; (3) a better use of the software tools (concerning drug interactions); (4) a better communication with the patient, however, that still needs further improvement. Beyond these results, this study opens up perspectives concerning continuous education for the pharmaceutical knowledge of pharmacists, and also on improving behaviour with patients.